Strategic implementation of a web-based business management software with radio frequency identification (RFID) data integration in a new fitness business through scenario building - Salen, Royce Kamille R.; Imbang, Glen A. (Quezon City University of the Philippines Diliman, Technology Management Center, 2013)
The Philippine fitness industry continues to grow, as more Filipinos become health conscious. Multiple fitness regimens are widespread in the country, and one of them that is currently trending is functional fitness. In the field of functional fitness, CrossFit is probably the most popular one. To date, there are about ten (10) official CrossFIt facilities in the country, majority of which are based in Metro Manila.
One of the most recently established CrossFit boxes (in CrossFit, the gym is referred to as a "box") in the country is CrossFit Alpha Strike, which is owned by seven entrepreneurs who are CrossFit coaches and enthusiasts. Even before it has arrived, its competitors have already established their names and gained popularity. Therefore, it is a challenge for Alpha Strike to standout and to gain a bigger market share.
What probably sets Alpha Strike apart is its innovativeness and openness to change. After probing on the current fitness and technology trends, it has decided to combine both while aiming to gain competitive advantage. It has adopted a web-based business management software with Radio Frequency ID (RFID) data integration, which is linked to its official website. Although a similar system is already out in the international market, it has innovated on its own system by customizing it and adding more features that add value to its customers. Not only that it could perform business processes more efficiently, but it could also acquire new members and increase retention rate because of the value added features it has incorporated in its system. Some of the features of the system are member management, online reservation, revenue and expense tracking, on-site greeter, leaderboard, blog and event posting, daily workout schedules, and members' lounge. Possible upgrades that are being looked at are a mobile app and real-time social tagging.
Alpha Strike has leveraged on technology to build competitive advantage. However, the success of its business depends on many complex factors. Through the help of scenario planning, a popular strategic planning method, multiple factors were identified as to come up with different scenarios that reflect the possible future of the implementation of the system. Respective strategies were formulated to address each of the scenario outcomes.
This study was able to show that Alpha Strike could achieve its short-term goal of innovating on its business and gaining competitive advantage through the implementation of a high technology system. Furthermore, recommendations based on the scenario outcomes and the respective strategies could serve as Alpha Strike's baseline for decision-making in its succeeding years of operations. This could help in achieving its long-term goals of maximizing profitability, sustaining business growth, and creating stability. This study has shown the importance of scenario building as it could be used as a technology foresight tool in strategic technology planning in organizations.
In partial fulfillment of the requirements of TM 299.
Thesis
Keywords: Radio frequency identification systems; Data integration (Computer science).